Exploring Reference Values for Hair Cortisol: Hair Weight Versus Hair Protein. - Frisch, Nadine; Eichler, Anna; Plank, Anne-Christine; Golub, Yulia; Moll, Gunther; Kratz, Oliver (Therapeutic Drug Monitoring, 2020)
BACKGROUND: As a marker of cumulative cortisol activity, hair cortisol has received attention in clinical and methodological research. Currently, it is a common practice to relate the hair cortisol concentration (HCC) to hair weight. This article explores the hair protein concentration (HPC) as another possible reference value for HCC. METHODS: For n = 18 hair samples cut from the posterior vertex, the HCC, HPC, and hair sample weight were determined, and the cortisol-to-weight and cortisol-to-protein ratios were calculated. Correlations were analyzed between the HCC, HPC, and hair sample weight as well as between the cortisol-to-weight and cortisol-to-protein ratios. Hair sample weight and HPC were included as independent variables in a stepwise linear regression model to predict HCC. RESULTS: The HCC and HPC did not correlate significantly (r = 0.393, P = 0.106); however, the correlation between HCC and hair sample weight was significant (r = 0.520, P = 0.027). The HPC and hair sample weight (r = 0.605, P = 0.008) as well as the cortisol-to-weight and cortisol-to-protein ratios (r = 0.858, P < 0.000) showed a high correlation. The hair sample weight was the better predictor of the HCC (β = 0.520, P = 0.027) than HPC (β = 0.125, P = 0.657). CONCLUSIONS: The results indicate that the hair sample weight is the more suitable reference value for the HCC. Thus, the standard cortisol-to-weight ratio should be used as the preferred expression for the cumulative cortisol activity measured in the scalp hair. However, calculating the cortisol-to-protein ratio can be considered as an alternative if the hair sample weight is not available.
EVALuna2:384364
Keywords: hair cortisol; hair protein; hypothalamic-pituitary-adrenal axis; methodology; stress